Letter to Editor: Comments on “Prediction of shock response for a quadrupod-mast using response spectrum analysis method - Rossit, Carlos Adolfo (2003)
Comments on “Prediction of shock response for a quadrupod-mast using response spectrum analysis method” by Cho-Chung Liang, Min-Fang Yang and Yu-Shiou Tai, 2002. Ocean Engineering 29, 887–914. The writers congratulate the authors for their thorough analysis which provides a valuable, useful reference for mast design. The mast constitutes Grade A equipment of a warship as correctly stated by the authors and, who use a cantilever beam attached to the shell plating to investigate the feasibility of the shock spectrum analysis method.